Dynamics of Leslie-Gower model with simplified Holling type IV functional response - Ali, Safaa Jawad; Md. Arifin, Norihan; Naji, Raid Kamel; Ismail, Fudziah; Bachok @ Lati, Norfifah (Watam Press, 2016)
In this paper a three-species of Leslie-Gower predatorprey food chain model with Holling type IV functional response is proposed. The dissipativeness of the solution of the model is discussed. Local and global stability analyses of the system are carried out. The dynamics of the predator-prey food chain model with simplified Holling type IV functional response is investigated theoretically and numerically.